Organizational level impact of teacher turnover on organizational climate, morale, turnover intentions and costs in public schools in the Sultanate of Oman - Al Balushi, Ruqaiya M. (2013)
Employee turnover is a pervasive and expensive phenomenon, costing organizations billions of dollars each year. The costs of turnover are not limited to monetary costs, since there are hidden costs incurred by the individuals, the employing organizations,and the society. The main purpose of this study is to investigate the impact of teacher turnover on organizational climate, organizational morale, turnover costs and turnover intentions of the remaining teachers in Omani public schools located in different geographical locations. Structural equation modeling was used to analyze the data collected through questionnaires and other means. In this study, several important findings were achieved. First, the average rate of teacher turnover in 2011 was 24%, which is high in comparison to Western studies. Second, in 2011, MOE in Oman incurred 2.8 million Omani Rials (about 7 million US$) for teacher turnover during that year (based on separation and replacement costs), and around 3.7 thousand Omani Rials (about 9.6 thousand US$) for the turnover of a single teacher. The highest costs were related to teacher separation, while the lowest costs were related to teachers’ recruitments procedures. Third, the study model was successful in obtaining several significant relationships between the study variables, such as: (1) a significant positive relationship between teacher turnover and turnover intentions (future turnover), (2) a significant positive relationship between organizational climate and organizational morale, (3) a significant negative relationship between organizational climate and intentions to quit, (4) a significant negative relationship between organizational climate and intentions to transfer, and (5) a significant positive relationship between teacher turnover and turnover costs. The current study may be useful in sparking the interest of turnover research in Omani and other Arabian countries since there are a scarcity of studies about teacher turnover and turnover consequences in these countries. The study results are specific to Omani public schools and generalization to Omani private schools and schools in other Arabian countries should be done with caution.